Power Flow Control of a Power Conversion Circuit for Contactless Power Transformer Systems with Coil Misalignment. Issue 1 (October 2015) - Kitazawa, Satoshi; Kondo, Keiichiro; Kashiwagi, Takayuki
SUMMARY The coupling coefficient between the coils of a noncontact power supply system is reduced by coil misalignment. This reduces the output voltage and the active power in the coils. To cope with these problems, an instantaneous current control method is applied to a single‐phase contactless power transformer system in order to apply the equivalent impedance of the PWM rectifier at the load side of the transformer. We propose a control method to supply power constantly to the load even when there is a misalignment in the receiving coils. The limit of the transferred power associated with the proposed control method is investigated. The proposed system, including the control method, is verified by experimental tests over a power range of several tens of watts.